Intralesional Injection of Measles, Mumps, and Rubella Vaccine in Molluscum Contagiosum Treatment: An Experimental Study - Karim, Sirwan Akram; Abdulla, Darsim Mohammed (Sulaimani Journal for Pure and Applied Sciences, 2022)
Molluscum contagiosum (MC) is a common viral infection that affects the skin and the mucous membranes. Several studies have shown that intralesional Measles, Mumps, and Rubella (MMR) immunotherapy is beneficial for treating warts. There is very little information about the effectiveness of this treatment method in patients with MC. The study's objective was to assess whether patients with MC benefit from intralesional MMR vaccination. This experimental study was carried out on 20 patients of MC (11 men and 9 women) who visited Sulaimani Dermatology Teaching Center, who received a maximum of six doses of intralesional MMR vaccine with an interval of two weeks between sessions. Three kinds of therapy responses were identified; complete, partial, and no response. A number of side effects were recorded. The mean ± SD of the age, duration of the disease, and the number of skin lesions were 17.9 ±17.1 years, 5.1 ±2.2 months, and 10.4 ±7.9 lesions, respectively. Sixty-five percent of patients had complete clearance, 25% with partial clearance and 10% experienced no clearance. According to the examined variables, no significant difference was present in the frequency of the various treatment responses (p>0.05). The noticed side effects were temporary mild redness, edema, and pain at the site of injection. Recurrence was not seen in any of the patients who responded completely to the treatment. Although it seems that intralesional MMR immunotherapy was effective and safe in the treatment of the skin lesions due to MC. To further support the results of the current study, larger prospective studies that are placebo-controlled and have longer follow-ups are required.
Keywords: Intralesional immunotherapy; MMR; Intralesional injection; Molluscum contagiosum; Vaccine